The Westward Dissemination of Pre-modern Chinese Book Collections to Europe - Zhou Yueshan (Ksiegarnia Akademicka Publishing, 2020)
One of the most magnificent collections of pre-modern Chinese books kept in Europe, was brought to France by Joachim Bouvet, a French missionary, in the 17th century. It is widely accepted that these 49 volumes of Chinese books were a gift from the Chinese emperor Kangxi to Louis XIV, the King of France, with Bouvet, the person who brought the books, believed to have been appointed as the Kangxi Emperor’s special envoy. However, as I intend to show here, it may be that neither was Bouvet a special envoy, nor were the books a gift from the Chinese emperor.